The Effects of Temperature Acclimation on Swimming Performance in the Pelagic Mahi-Mahi (Coryphaena hippurus) - Heuer, Rachael M.; Stieglitz, John D.; Pasparakis, Christina; Enochs, Ian C.; Benetti, Daniel D.; Grosell, Martin (Frontiers in Marine Science, 2021)
Mahi-mahi (Coryphaena hippurus) are a highly migratory pelagic fish, but little is known about what environmental factors drive their broad distribution. This study examined how temperature influences aerobic scope and swimming performance in mahi. Mahi were acclimated to four temperatures spanning their natural range (20, 24, 28, and 32°C; 5–27 days) and critical swimming speed (Ucrit), metabolic rates, aerobic scope, and optimal swim speed were measured. Aerobic scope and Ucrit were highest in 28°C-acclimated fish. 20°C-acclimated mahi experienced significantly decreased aerobic scope and Ucrit relative to 28°C-acclimated fish (57 and 28% declines, respectively). 32°C-acclimated mahi experienced increased mortality and a significant 23% decline in Ucrit, and a trend for a 26% decline in factorial aerobic scope relative to 28°C-acclimated fish. Absolute aerobic scope showed a similar pattern to factorial aerobic scope. Our results are generally in agreement with previously observed distribution patterns for wild fish. Although thermal performance can vary across life stages, the highest tested swim performance and aerobic scope found in the present study (28°C), aligns with recently observed habitat utilization patterns for wild mahi and could be relevant for climate change predictions.